PENGELOLAAN KELAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Fadhilah, Nurul; Rohmatullah, Rohmatullah; Mutaqin, Mumu Zainal (LPPM STAI Al-Azhary Cianjur, 2024)
This research aims to examine more deeply about classroom management in Islamic Religious Education (PAI) learning using the literature study method. The main aim of this research is to understand and analyze the various strategies and approaches that have been used in managing PAI classes. The literature study method was chosen as a research approach because it can collect, analyze and synthesize information from various relevant sources. In this research, researchers will conduct a review of various literature that has been published regarding PAI classroom management. Researchers will analyze the strategies and approaches that have been used by educators in managing PAI classes, as well as evaluate the effectiveness of these methods. It is hoped that the results of this research can provide better insight into classroom management in PAI learning. With a better understanding of effective strategies and approaches, educators can improve the quality of PAI learning and create a classroom environment that is conducive for students in studying the Islamic religion. Thus, this research has the potential to make a positive contribution to the development of Islamic religious education in Indonesia.